Exploring Speaking Skills through the Experience-Based Contextual Hybrid Learning (EXCHIL) Model among English Education Students - Dwi Nopiyadi; Lili Sururi Asipi; Mochamad Guntur; Indah Puspitaningsih; Angga Adi Saputra (Journal of General Education and Humanities, 2025)
This study aims to examine the effectiveness of the EXCHIL Model (Experience-Based Contextual Hybrid Learning) in improving the speaking skills of students in the English Language Education Study Program at Institut Prima Bangsa. Using a convergent parallel mixed-methods design with a descriptive approach, the study involved 52 students. Quantitative data were obtained through questionnaires and pre-test–post-test scores, while qualitative data were collected from observations and in-depth interviews with three students. The main challenges identified were limited vocabulary, pronunciation difficulties, and speaking anxiety. Results showed a substantial improvement in students’ speaking performance, with the average pre-test score of 66.2 to 82.4 in the post-test. The score distribution also shifted positively, as more students achieved scores in the 75–85 range, while fewer scored below 70. Qualitative findings revealed enhanced fluency, confidence, and willingness to speak after the implementation of the model. These findings suggest that integrating experiential, contextual, and hybrid elements can foster student-centered language learning adaptable to diverse digital environments. Overall, the results highlight the potential of the EXCHIL Model for advancing 21st-century EFL pedagogy.